Effect of grafted graphene nanosheets on morphology evolution and conductive behavior of poly(methyl methacrylate)/poly(styrene-co-acrylonitrile) blends during isothermal annealing. Issue 26 (18th April 2018) - Zhang, Jifei; Zuo, Min; Lv, Xiong; Zhang, Haimo; Zheng, Qiang
Abstract : The activation energy of conductive pathway formation for PMMA/SAN/PMMA- g -RGO nanocomposites is close to that of flow for PMMA, indicating that DC percolation is mainly related to the mobility of grafted PMMA chains, rather than that of SAN chains. Abstract : A facile method was developed for directly grafting poly(methyl methacrylate) (PMMA) to graphene oxide (GO) without surface modification, with the resultant insulating PMMA- g -GO nanosheets further reduced in situ to give conductive grafted reduced graphene oxide (RGO) nanosheets. The effect of PMMA- g -RGO nanosheets on the morphological evolution and conductive behavior of partially miscible blends of poly(methyl methacrylate)/poly (styrene- co -acrylonitrile) (PMMA/SAN) upon annealing above their phase-separation temperature was investigated using phase-contrast microscopy (PCM) with a real-time online digital picoammeter. With phase separation of the blend matrix, the well-dispersed PMMA- g -RGO nanosheets in the homogeneous matrix preferentially migrated to the SAN-rich phase and showed remarkably little aggregation. Surface grafting of PMMA- g -RGO might inhibit the aggregation of nanosheets in the blend matrix and weaken the retardation effect of nanosheets on the morphology evolution of the blend matrix. Furthermore, the percolation behavior of dynamic resistivity for ternary nanocomposites was attributed to the formation of a PMMA- g -RGO conductive network in the SAN-rich phase. The activation energy of conductive pathway formation was closer to the activation energy of flow for PMMA than that of SAN.